Perancangan dan Implementasi Video Profile Jurusan RPL di SMK Globe National Plus 2 Batam - Jimmy Pratama; Brenky Jie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
Along with the rapid development of technology, the utilization of information technology for advertising or promoting products has increased, enabling products to be recognized faster by the public. One way to introduce a product to the public is by creating a video profile of a school. Through the video profile, the public can get to know the school more easily. SMK Globe National Plus 2 Batam, managed by Yayasan Batam Bumi Cemerlang, faces challenges as it does not have a video profile to introduce and promote the Software Engineering (RPL) department. Therefore, the creation of a video profile is needed to introduce and promote the RPL department. In this video profile design, the author applies the MDLC (Multimedia Development Life Cycle) method and uses Adobe Premiere Pro software. The results of this research are expected to assist the school in promoting and introducing the RPL department more effectively.